2021
DOI: 10.1002/dvdy.393
|View full text |Cite
|
Sign up to set email alerts
|

Chordacentrum mineralization is delayed in zebrafish betaglycan‐null mutants

Abstract: Background The Transforming Growth Factor β (TGFβ) family is a group of related proteins that signal through a type I and type II receptors. Betaglycan, also known as the type III receptor (Tgfbr3), is a coreceptor for various ligands of the TGFβ family that participates in heart, liver and kidney development as revealed by the tgfbr3‐null mouse, as well as in angiogenesis as revealed by Tgfbr3 downregulation in morphant zebrafish. Results Here, we present CRISPR/Cas9‐derived zebrafish Tgfbr3‐null mutants, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…We have demonstrated that in the null tgfbr3 zebrafish there is a delay in the mineralization of the chordocentra, the vertebrae primordia, and have proposed that this delay is due to the absence of TGFβ signaling enhancement, a function that has been well documented for this co-receptor. 19 However, given the many biochemicals activities that have been found in vitro for Tgfbr3, it is hard to propose a specific role for its selective expression in the adaxial cells and the SSM, particularly, given its A-P gradient expression documented in Figure 7. It is tempting to hypothesize that tgfbr3 expression is not only responding to a morphogen gradient but may help creating such a gradient.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have demonstrated that in the null tgfbr3 zebrafish there is a delay in the mineralization of the chordocentra, the vertebrae primordia, and have proposed that this delay is due to the absence of TGFβ signaling enhancement, a function that has been well documented for this co-receptor. 19 However, given the many biochemicals activities that have been found in vitro for Tgfbr3, it is hard to propose a specific role for its selective expression in the adaxial cells and the SSM, particularly, given its A-P gradient expression documented in Figure 7. It is tempting to hypothesize that tgfbr3 expression is not only responding to a morphogen gradient but may help creating such a gradient.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this time of initial mCherry expression matches with the time of appearance of tgfbr3 mRNA as detected by RT-PCR. 19 By 14 hpf, mCherry is observed in the eye and mesoderm, including the somites (Figure 4D). At 24 hpf, the reporter expression starts to be confined to specific structures like heart, pronephric duct, eyes, and the somites where it adopts a chevron like arrangement (Figure 4E) which becomes very evident at later stages (Figure 4H).…”
Section: Zebrafish Tgfbr3 Promoter Is Turned On Shortly Before the St...mentioning
confidence: 97%
See 3 more Smart Citations